Aprimoramento de um robô lutador de sumô autônomo - Zielinski, Kallil Miguel Caparroz (2018)
The automated robotization in the industrial production is one of the factors that have been strongly altered in the globalization process of the last few years. The robots, even going through maintenance, are more beneficial to the enterprises, because they have remarkable precision of results, faster production, low labor costs, uninterrupted production, better finishing quality, among many other factors. Robotics researchers focus their efforts on mobile robots to react appropriately to the environment, opening a vast field of new applications and consequently many challenges. This project details the improvement of an autonomous sumo robot, changing from its mechanical structure to its logic of locomotion, using the supervisory control theory proposed by Ramadge and Wonham in 1989 for this, replacing sensors and actuators, improving the motor drivers and applying defense strategies in order to obtain the best possible result.